MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BIMBINGAN KONSELING PADA SMP NEGERI 17 BANDA ACEH - Yuharti .; Muniarti AR; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The objective of this research was to find out the principal’s planning in improving the performance of the guidance and counseling teachers at State Junior High School (SMP Negeri) 17 Banda Aceh by observing the personality of each teacher. The data were collected by doing direct observation and interview with the principal, the vice-principal, the school supervisors, and the guidance and counseling teachers of State Junior High School (SMP Negeri) 17 Banda Aceh. The sampling technique, the observation, and the interview in collecting the data was equipped with a list of questions that is able to find out the information related to the activity of supervising teachers done by the principal of State Junior High School (SMP Negeri) 17 Banda Aceh. The results indicated that the guidance and counseling teachers, the principal and the staffs were involved in compiling the planning of guidance and counseling program. This involvement gave positive impact on the effectiveness of the program. In addition, the guidance and counseling teachers have showed good performance and mature personality. However, the strategies in improving the performance of guidance and counseling teachers such as providing a special room for guidance and counseling activities and scheduling guidance and counseling subject for each class should be more considered. Keywords: principal’s management, guidance and counseling teacher’s performance